Pemberdayaan Masyarakat Bisu Tuli: Studi Kasus Program KEM Bengkala PT Pertamina DPPU Ngurah Rai - Arifin, Muhson; Rainday Ahmad, Yusnur; Hartato, Muhammad; Hardiyanti Utami, Dhita; Paramitasari, Ahsani (LPkM Universitas Bakrie, 2022)
World Federation of the Deaf (WFD) shows that there are 70 million deaf people worldwide but only about 2% of deaf people can access education using sign language and only 20% of deaf people in developing countries get access to education. Deaf people also have difficulties in accessing the economic sector. This is also experienced by the people of Bengkala Village, that also known as the Deaf Village due to the birth rate of the deaf people in this village is 1.14% and it is higher than the birth rate of deaf people in the world. PT Pertamina DPPU Ngurah Rai in order to increase the community inclusiveness, as well as empowering deaf people to get decent education and jobs, has organized a CSR program called KEM Bengkala. This study aims to explore and take a deeper look at the implementation and impact of the KEM Bengkala program implementation. By using qualitative research methods and a case study approach, it is expected to be able to explore deeper and more thorough data. The results of the research show that through KEM Bengkala program, PT Pertamina DPPU Ngurah Rai has succeeded in increasing the capacity of deaf people of Bengkala Village. They have been able to produce weaving, incense, ingka (skewer plate), and Sakuntala herbal medicine. Deaf people of Bengkala through this program can also develop local dances of Bengkala Village, they are Jalak Anguci, Yogi Nandhini, Janger Kolok, Puspa Arum, and Bebila Dance. These programs can run well and create program sustainability by involving 3 sectors from the government, civil society, and companies.